Atrial septal defect: Its past, present, and future - ÇİMEN, Serdar and GÜNAY, Rafet and DEMİRTAŞ, Murat and KETENCİ, Bülend and ÖZAY, Batuhan (Cerrahpaşa Medical Journal, 2014)
Atrial Septal Defekt is the interatrial defect that occurs in atrial septum that leads to an abnormal shunting. Although it can be seen mostly as an isolated anomaly, it can also appear with major cardiac anomalies. It occurs mostly asymptomatic, however in infantile period congestive heart failure can be seen. The treatment of ASD ranges from medical to surgical treatment. The symptoms and comorbidities help us to evaluate the way of treatment. As can be performed in all ages with less risk and excellent long term results, surgery is the standard treatment. Nowadays, percutaneous transcatheter closure of the defect becomes a popular way of treatment and it seems that it will be the first choice of treatment for suitable cases in near future.